A atuação do assistente social no trato com adolescentes em conflito com a lei: possibilidades para uma intervenção profissional crítica no espaço sociojurídico, (TJSP) - Moreira, Luis Charles (2016)
The work of the social worker in the social legal system is scheduled to be directed by the demands of the institution in which the professional is inserted, an integral part of the symbolic ritual that takes place in the internal processes of the judiciary; such proceedings are intended to induce a feeling of "doing justice", and are expressed in its most complete form, by the decision of the Judge. In this context, in preparing reports and technical advice to assist the magistrate, the social worker is integrated into the judicial apparatus. On Juvenile Justice, with respect to proceedings regarding infractions such symbolic rituals have repercussions that are observed in the form in which the treatment of adolescents in conflict with the law by judicial actors. Sometimes the indifference to the real needs of adolescents is perceived in the way these voice is stifled before the Power and Institutional Violence Demonstrations in socio-juridical spaces. This study revolves around the role of the social worker in the Forum of sticks Specials for Children and Youth of São Paulo, highlighting the "Light Project Youth" noting the possibilities, by the team Judicial Technical Social Services, this Forum , to overcome an apparent complicity condition to the capitalist state domination project, a condition that emerges, albeit unintentionally, when its performance is mixed to all other internal processes of the judiciary, following only the demands imposed themselves institutionally. The Project being built by social workers in this sociojurídico environment, it is observed that these, drawing on his professional relative autonomy, seek to make a critical and emancipatory action within the judicial apparatus, starting from a professional practice that seeks the development of reflexive movements in the bias of critical theory, the subjects objects of intervention, stressing, therefore, the privileged position of mediation through art in this process. With this practice, the professionals seek to build new proposals intervening for their professional activities at the same time assume a position of resistance to the conditions imposed by a domination project, which is consistent with the proposed construction of a new social order , as shown in Ethical-Political Project of the social worker